Work Self-Efficacy in Strengthening Employee Psychological Well-Being: Systematic Review and Future Direction - Irsyaadan Azhar, Wahyu; Niska Dinda Nadia, Fiona (DINASTI RESEARCH, 2025)
This study aims to conduct a systematic review of the relationship between work self-efficacy and employee psychological well-being. Although many previous studies have been conducted, there is still a limitation in comprehensive studies on this topic. Using the guidelines of Tranfield et al. (2003), this study identified and analyzed relevant articles from the Scopus database, focusing on the context of psychological well-being. The search results showed that out of 261 articles identified, 63 articles were not relevant and 18 articles were selected for further analysis. The findings indicate that self-efficacy plays an important role in improving employee psychological well-being, as well as identifying research gaps and future research directions. This study is expected to provide better insight into work self-efficacy and its implications for organizations.